Students’ Self Efficacy on Bahasa Inggris 2 at Teacher Education of Islamic Primary School Study Program of IAI DDI Polewali Mandar - Afiah, Nur (UI DDI AGH AD Polewali Mandar, 2018)
This study is a report of an investigation into how various sources of self-efficacy information influence of students’ perceptions of self-efficacy at Bahasa Inggris 2 Course. Design of this research is a case study, especially observational case study. Three students of fourty-six from Teacher Education of Islamic Primary School Study Program of IAI DDI Polewali Mandar in participated in this research. From this study we determined that students individually displayed consistent experiences of efficacy change in their responses to the questionnaire and interviews. Mastery experiences were the most powerful efficacy source in Bahasa Inggris 2 course.